Analysis of Green Buying Behavior Among Young Iphone Users in Yogyakarta - Tengger Pinandhito (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This study aims to examine the variables of interpersonal influence and environmental knowledge mediated by environmental attitudes that can influence green purchasing behavior in young consumers who use iPhones in the Special Region of Yogyakarta with a sample of 156 respondents. The analysis technique used in this study is structural equation modeling (SEM) analysis processed with IBM SPSS AMOS 24 and data collection using purposive sampling technique. The results of this study indicate a positive influence of interpersonal influence and environmental knowledge on environmental attitudes and green purchasing behavior, and also a positive influence of attitudes towards the environment on green purchasing behavior in young consumers who use iPhones in Yogyakarta.